Activation of the CED3/ICE-Related Protease CPP32 in Cerebellar Granule Neurons Undergoing Apoptosis But Not Necrosis - Armstrong, Robert C. (J Neurosci, 1997)
Neuronal apoptosis occurs during nervous system development and after pathological insults to the adult nervous system. Inhibition of CED3/ICE-related proteases has been shown to inhibit neuronal apoptosisin vitro and in vivo, indicating a role for these cysteine proteases in neuronal apoptosis. We have studied the activation of the CED3/ICE-related protease CPP32 in two in vitro models of mouse cerebellar granule neuronal cell death: K(+)/serum deprivation-induced apoptosis and glutamate-induced necrosis. Pretreatment of granule neurons with a selective, irreversible inhibitor of CED3/ICE family proteases, ZVAD-fluoromethylketone, specifically inhibited granule neuron apoptosis but not necrosis, indicating a selective role for CED3/ICE proteases in granule neuron apoptosis. Extracts prepared from apoptotic, but not necrotic, granule neurons contained a protease activity that cleaved the CPP32 substrate Ac-DEVD-aminomethylcoumarin. Induction of the protease activity was prevented by inhibitors of RNA or protein synthesis or by the CED3/ICE protease inhibitor. Affinity labeling of the protease activity with an irreversible CED3/ICE protease inhibitor, ZVK(biotin)D-fluoromethylketone, identified two putative protease subunits, p20 and p18, that were present in apoptotic but not necrotic granule neuron extracts. Western blotting with antibodies to the C terminus of the large subunit of mouse CPP32 (anti-CPP32) identified p20 and p18 as processed subunits of the CPP32 proenzyme. Anti-CPP32 specifically inhibited the DEVD-amc cleaving activity, verifying the presence of active CPP32 protease in the apoptotic granule neuron extracts. Western blotting demonstrated that the CPP32 proenzyme was expressed in granule neurons before induction of apoptosis. These results demonstrate that the CED3/ICE homolog CPP32 is processed and activated during cerebellar granule neuron apoptosis. CPP32 activation requires macromolecular synthesis and CED3/ICE protease activity. The lack of CPP32 activation during granule neuron necrosis suggests that proteolytic processing and activation of CED3/ICE proteases are specific biochemical markers of apoptosis.